2017
DOI: 10.1177/1528083717716168
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and comfort properties of hydroentangled nonwovens from comber noil

Abstract: Cotton fibre is one of the most important commodity fibre and is widely employed in apparels. At present, the share of natural fibres in production of nonwoven fabrics is low and employed in opt applications. The cotton fibre is conventionally converted into woven and knitted fabrics by short staple spinning methods. The comber noil is short fibre waste during production of combed cotton yarns. The aims of the current study were to employ comber noil for preparation of hydroentangled cotton nonwovens at varyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…Hydroentanglement technology is usually used to produce cotton-based nonwovens because it not only allows the bonding of fibrous web but also helps the additional cleansing of cotton fibres. A recent study explored the potential of using comber noil (a by-product from the production of fine-quality combed-cotton yarns) to produce hydro-entangled nonwovens for hygiene and healthcare applications [206]. The results of this study showed that hydro-entangled nonwovens from comber noil could potentially be employed in disposable applications.…”
Section: Cotton In Technical Textilesmentioning
confidence: 94%
“…Hydroentanglement technology is usually used to produce cotton-based nonwovens because it not only allows the bonding of fibrous web but also helps the additional cleansing of cotton fibres. A recent study explored the potential of using comber noil (a by-product from the production of fine-quality combed-cotton yarns) to produce hydro-entangled nonwovens for hygiene and healthcare applications [206]. The results of this study showed that hydro-entangled nonwovens from comber noil could potentially be employed in disposable applications.…”
Section: Cotton In Technical Textilesmentioning
confidence: 94%
“…Ahmad and his colleagues studied the use of comber noil in the production of hydroentangled nonwovens at varying water jet pressures and conveyor speeds. The results showed that these variables can help to manufacture fibrous assemblies with engineered properties, according to required application area [10]. The effect of laying directions on the mechanical and comfort properties of nonwoven fabrics produced with 100% polyester, and polyester/viscose blended was investigated [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…It can produce homogeneous nonwoven textile products [13,14,15,16,17]. The hydroentanglement technique is one of the mechanical bonding techniques that uses fine high-pressure water jets that strike a web to rearrange and entangle fibers, capable of producing nonwovens with good wet strength and softness and high-water absorbency [18,19,20,21]. The wet strength and dispersibility of wet-laid hydroentangled nonwovens depend on raw fiber materials and process parameters, such as fiber length and water jet pressure [22].…”
Section: Introductionmentioning
confidence: 99%